2019
DOI: 10.1002/hbm.24846
|View full text |Cite
|
Sign up to set email alerts
|

Primary auditory cortex representation of fear‐conditioned musical sounds

Abstract: Auditory cortex is required for discriminative fear conditioning beyond the classical amygdala microcircuit, but its precise role is unknown. It has previously been suggested that Heschl's gyrus, which includes primary auditory cortex (A1), but also other auditory areas, encodes threat predictions during presentation of conditioned stimuli (CS) consisting of monophones, or frequency sweeps. The latter resemble natural prosody and contain discriminative spectro-temporal information. Here, we use functional magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
4
10
0
Order By: Relevance
“…However, we did not find clear evidence that the role of S1 in threat conditioning and threat-memory retention differed between simple and complex somatosensory stimuli (here differentiated by the temporal pattern of the stimulus across one or two fingers). On the other hand, our findings are in line with human neuroimaging studies that found equal CS+/CS-neural pattern discriminability for simple and complex CS in the auditory cortex 34,35 and that were able to cross-decode simple CS threat predictions from complex threat predictions and vice versa 34 . However, it is possible that experiments with larger sample sizes may yet detect such complexity effects 62,63 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we did not find clear evidence that the role of S1 in threat conditioning and threat-memory retention differed between simple and complex somatosensory stimuli (here differentiated by the temporal pattern of the stimulus across one or two fingers). On the other hand, our findings are in line with human neuroimaging studies that found equal CS+/CS-neural pattern discriminability for simple and complex CS in the auditory cortex 34,35 and that were able to cross-decode simple CS threat predictions from complex threat predictions and vice versa 34 . However, it is possible that experiments with larger sample sizes may yet detect such complexity effects 62,63 .…”
Section: Discussionsupporting
confidence: 91%
“…In human studies, threat-predictive CS+ and safe CS− elicit differential evoked-potential amplitude, oscillatory synchrony, and univariate fMRI BOLD amplitude in visual cortex [29][30][31] , multivariate BOLD patterns in olfactory cortex 32 , and univariate BOLD amplitude as well as multivariate patterns in the auditory cortex, with no difference between simple and complex CS [33][34][35] .…”
Section: Introductionmentioning
confidence: 95%
“…It is of course theoretically possible for a listener to develop a learned aversion for previously neutral sounds (as a result of past events), which might ultimately lead to elevated unpleasantness when exposed to these sounds. Findings from research in mice [21] and human listeners [22] suggest that such a learned aversive valence for acoustic signals may then be reflected by neural responses in the AC. Given that activation in AC was not better explained by unpleasantness relative to the other two variables in the present study, though, our data do not support the idea that learned aversion played an important role with respect to listeners' unpleasantness ratings.…”
Section: Activation In Relation To Sound Level Loudness and Unpleasamentioning
confidence: 99%
“…20]. Other studies suggest that a learned aversive valence for sounds (e.g., through fear conditioning), which might be the cause of a higher unpleasantness in some cases, is reflected by altered AC activity [e.g., 21,22]. Given that activation in response to LFS and IS appears to be very similar to that of typical audio sound, we hypothesized that fMRI is a suitable tool to disentangle the representation of loudness and unpleasantness and to identify interindividual differences in the perception of LFS and IS.…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate analysis of high-resolution fMRI might be more appropriate to delineate such representations [43][44][45] . Table 1).…”
Section: Discussionmentioning
confidence: 99%